Analysis and experiments with a 3D printed walking robot to improve climbing obstacle. (8th June 2020) - Chavdarov, Ivan; Krastev, Aleksandar; Naydenov, Bozhidar; Pavlova, Galia
The purpose of this work is to investigate the possibilities of climbing higher obstacles while maintaining the overall dimensions of a walking robot through design improvements and experiments. An original concept for the design of a walking robot with a minimum number of motors is presented. Geometric and force constraints for overcoming an obstacle and the conditions for maintaining static stability are determined. Experiments for overcoming a vertical obstacle are conducted with a 3D printed model. The 3D printed robot feet with different shapes and materials are used. The results of the experiments are presented graphically as a percentage of success against a baseline model. In this study, a dimensionless index to compare the height of the overcome obstacle and the dimensions of the robot is introduced. It allows to objectively compare the possibilities of overcoming obstacles between various types of mobile robots. Conclusions and guidelines for design improvements are made.